Native Turfgrass Tolerance to Indaziflam Applications - J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2017)
Multiple research trials were conducted from 2014 to 2016 in the Manhattan, KS, area to determine the use of indaziflam in native turfgrass systems. Results indicated that evaluated species are tolerant to indaziflam applications throughout the year.
Keywords: Native turfgrass; indaziflam; Specticle